Search for Chemosensors for Fluoride Ions: A Highly Promising Area of Research - Yadav, Pramod Kumar (Academic Voices: A Multidisciplinary Journal, 2015)
In recent times, chemosensors for fluoride ions have attracted a great deal of attention. Fluoride ions play an important role in many biological, industrial and environmental processes and are associated with diseases like Alzeimer’s disease. This paper covers imidazole, indole, azo-phenol and benzohydrazide based chemosensors for F-ion with synthesis and detection methods. DOI: http://dx.doi.org/10.3126/av.v4i0.12356 Academic Voices Vol.4 2014: 42-44